Dioxovanadium(V) Complex Incorporating Tridentate ONO Donor Aminobenzohydrazone Ligand: Synthesis, Spectral Characterization and Application as a Homogeneous Lewis Acid Catalyst in the Friedländer Synthesis of Substituted Quinolines. (21st October 2022) - Kargar, Hadi; Fallah-Mehrjardi, Mehdi; Munawar, Khurram Shahzad
Abstract: A dioxovanadium complex has been successfully prepared by the reaction of an ONO-donor Schiff base, derived by condensing aminobenzohydrazide and 3-ethoxysalicylaldehyde, with VO2 (acac)2 . The structures of synthesized products were explored spectroscopically through FT-IR, 1 H & 13 C NMR, and by elemental composition (CHN) through combustion analysis. The catalytic potential of the complex was explored for the synthesis of substituted quinolines by adapting the Friedländer method. In this method, a cyclocondensation reaction of ortho aminoaryl aldehydes or ketones was carried out with another ketone having an alpha methylene group under solvent-free conditions. The main advantages of the present catalytic work are less time required for the completion of the reaction, high percentage yield, and easy work out procedure.